2017
DOI: 10.3389/fimmu.2017.00617
|View full text |Cite
|
Sign up to set email alerts
|

FTR83, a Member of the Large Fish-Specific finTRIM Family, Triggers IFN Pathway and Counters Viral Infection

Abstract: Tripartite motif (TRIM) proteins are involved in various cellular functions and constitute key factors of the antiviral innate immune response. TRIM proteins can bind viral particles directly, sending them to degradation by the proteasome, or ubiquitinate signaling molecules leading to upregulation of innate immunity. TRIM proteins are present in across metazoans but are particularly numerous in vertebrates where genes comprising a B30.2 domain have been often duplicated. In fish, a TRIM subset named finTRIM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…The case of fintrim [ 16 , 36 ] is particularly interesting: discovered as VHSV- and IFN- induced genes in rainbow trout leukocytes [ 16 ], they display signatures of positive selection suggesting that they may be involved in the antiviral response [ 36 ]. However, a direct IFN-dependent antiviral activity has been shown for only one member of this large gene family in zebrafish [ 37 ], and it is not clear whether all fintrim are actually involved in the IFN response. Our observations also suggest that a number of fintrim , which are induced similarly in A22 and B57, may play a role in the antiviral defense independently of the IFN response, a possible strategy to counteract viral subversion strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case of fintrim [ 16 , 36 ] is particularly interesting: discovered as VHSV- and IFN- induced genes in rainbow trout leukocytes [ 16 ], they display signatures of positive selection suggesting that they may be involved in the antiviral response [ 36 ]. However, a direct IFN-dependent antiviral activity has been shown for only one member of this large gene family in zebrafish [ 37 ], and it is not clear whether all fintrim are actually involved in the IFN response. Our observations also suggest that a number of fintrim , which are induced similarly in A22 and B57, may play a role in the antiviral defense independently of the IFN response, a possible strategy to counteract viral subversion strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations also suggest that a number of fintrim , which are induced similarly in A22 and B57, may play a role in the antiviral defense independently of the IFN response, a possible strategy to counteract viral subversion strategies. Further investigations will be necessary to understand the diversity of the antiviral mechanisms mediated by these highly diversified factors [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ISGs are found only among the recently diversified, species-specific finTRIMs; the most basal members (ftr82-84), well-conserved among fish, were not found here to be induced by IFNφ1 or by CHIKV, consistent with previous studies (48). Nevertheless, ftr83 appears to mediate protection especially in the gill region by stimulating local ifnphi1 expression (49). The diversity and evolution under positive selection of the IFN-inducible finTRIMs evoke viral recognition (22), yet their functions remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The RING domain of TRIMs usually mediates interaction with ubiquitin-conjugating enzyme (E2) via zinc finger motifs (Ye and Rape 2009;Ebner et al 2017;Esposito et al 2017). Several studies have shown that the RING domain is essential for the antiviral activity of the TRIM members, including TRIM5a, TRIM56, TRIM41, TRIM25, and ftr83 (Zhang et al 2013;Liu et al 2014;Campbell et al 2015;Yang et al 2016a;Langevin et al 2017). Several TRIM-like members, such as TRIM14 and TRIM16 lack a RING domain within the RBCC (Bell et al 2012;Zhou et al 2014), but fish TRIM16 has a RING domain while not possessing a B-Box domain (Yu et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of ftr83 promotes the infection of some RNA viruses, including Infectious hematopoietic necrosis virus (IHNV), viral hemorrhagic septicemia virus (VHSV), and SVCV. However, ftr82 did not play any role in viral infection, although engaged in zebrafish vascular patterning (Chang et al 2017;Langevin et al 2017).…”
Section: Introductionmentioning
confidence: 95%